Konflik Perbatasan Indonesia-Malaysia Dalam Forum Komunitas Online Dan Perspektif Masyarakat Di Wilayah Perbatasan - Irwansyah Irwansyah (Postgraduate of Jayabaya University, 2016)
The boundary conflict of Indonesia and Malaysia always related with the differences in perceptions, understanding and responses. Therefore, by using the concept of communicate conflict from Krauss and Morella, this study analyzes the new media and social media-based online discussion forums to find the border issue which often becomes discourse. By using nethnography, texts discourse that causes differences in perception, understanding, and construction is analyzed and then compared with the findings of the actual state of border areas with ethnographic methods. Combined nethnographic and ethnographic methods in collecting, processing, analyzing and discussing the data potential conflict border areas of Indonesia and Malaysia are expected to find and decipher the Indonesia-Malaysia conflict truth. This research shows that online discussion forum users do not understand the context of boundary, while the local community shows that the harmonization of interaction and communication. Conflict in the online community forum is an extension Indonesia-Malaysia bilateral conflict has actually been completed.